Effect of Atmospheric Cold Plasma Treatment on the Microorganism Growth, Diversity, and Quality of Coconut Water During Refrigerator Storage - Lixian Zeng; Wenyue Gu; Yuanyuan Wang; Wentao Deng; Jiamei Wang; Liming Zhang (Foods)
To study the effect of cold plasma (CP) on the refrigerator shelf life of coconut water, microorganism growth and diversity and physicochemical properties were investigated. Results indicated that CP treatment did not cause significant color changes in coconut water, with turbidity remaining lower than the control even after 6 days of storage. Enzymatic activity analysis revealed reduced polyphenol oxidase (PPO) and peroxidase (POD) levels in treated samples. Specifically, the 12 s CP treatment resulted in the lowest antioxidant capacity values: 15.77 Fe2+/g for ferric reducing antioxidant power (FRAP), 37.15% for DPPH radical scavenging, and 39.51% for ABTS+ radical scavenging. Microbial enumeration showed that extended CP treatment effectively inhibited the growth of total viable counts, psychrophilic bacteria, lactic acid bacteria, and yeast. High-throughput sequencing identified Leuconostoc, Carnobacterium, and Lactobacillus as the dominant bacterial genera. During storage, Carnobacterium was the primary genus in the early stage, while Leuconostoc emerged as the dominant genus by the end of the storage period. In summary, CP as an effective non-thermal technology was able to maintain quality and antioxidant capacity, inhibit microbial growth, and delay the spoilage in coconut water to help extend the refrigerated shelf life of the product.